Evaluation of tumor load in sentinel lymph node in patients with cutaneous melanoma - PEDRO DEAK DE ALMEIDA; LUCCAS LAVAREZE; CAROLINA EMERICK DA SILVA RANGEL; FERNANDA VIVIANE MARIANO; DIEGO VICTOR NUNES RODRIGUES; TIAGO ANTONIO BALDASSO; RENATO VENTURA FANNI; ANDRE LUIS MAION CASARIM; ANDRÉ DEL NEGRO; ALFIO JOSÉ TINCANI (Revista do Colégio Brasileiro de Cirurgiões, 2023)
ABSTRACT Introduction: cutaneous melanoma (MC) is a malignant neoplasm derived from melanocytic cells with an aggressive behavior. It is usually associated with the multifactorial interaction of genetic susceptibility and environmental exposure, usually ultraviolet radiation. Despite advances in treatment, the disease remains relentless with poor prognosis. Sentinel lymph node (SLN) biopsy is a technique used to screen patients in need of lymph node dissection. Objectives: to correlate the tumor burden in the SLN with the mortality of patients undergoing SLN biopsy. Methodology: the medical records and histological slides of patients with MC who underwent SLN biopsy treated at HC-Unicamp from 2001 to 2021 were retrospectively analyzed. The positive SLN were measured according to the size of the tumor infiltration area, for analysis of the depth of invasion (DI), closest proximity to the capsule (CPC) and tumor burden (TB). For statistical analysis, associations between variables were analyzed using Fishers exact test, with post Bonferroni test and Wilcoxon test. Results: 105 records of patients who underwent SLN biopsy of MC were identified. Of these, nine (8.6%) had positive SLN and 81 (77.1%) had negative SLN. The performed lymphadenectomies resulted in 55.6% (n=5) affected, 22.2% (n=2) without disease and 22.2% (n=2) were not performed. Mean CPC, TB, and DI were 0.14mm, 32.10mm and 2.33mm, respectively. Patients with T2 and T3 tumors were more likely to show the SLN affected (p=0.022). No patient with positive SLN died during follow-up. Conclusion: patients who presented T3 staging are the ones who most presented positive SLN.